Respuestas

2013-11-12T23:47:16+01:00
X+1/x+3 + x-3/x-1 =5/4 factor común:                                                                        4(X+3) (X-1) 4(x-1)(x+1) + 4(x+3(x-3)) = (x +3)(x-1)5 (4x-4)(x+1) +(4x+12)(x-3) = (x+3)(5x-5) 4x2 -4 ´+4x2 -36 = 5x2 +10x -15 4x2 -4 ´+4x2 -36- 5x2 -10x +15 = 0 3x2 -10x -25 = 0 Donde : a=3, b=-10 y c =-25 X=10 ± √ (-10)2 -4(3)(-25)         =  10 ± √ 100 +300       =   10 ± √ 400         = 10 ± 20                          2(3)                                      6                                 6                          6     Luego: x1  = 10 +20        = 30 / 6  = 5              x= 10 -20       =  -10/6  = -5/3                            6                                                              6  
2) 6/x-1 + x+1/x-1 -6 = 0  Se resuelve de igual manera que la anterior